Ray Kroc’s Interactional Styles Features in Business Conversation in The Founder - Cindy Melani Pratikno (Institute of Research and Community Outreach - Petra Christian University, 2022)
This study focuses on the features of interactional styles used by Ray Kroc, the male main character, when in a business conversation with others in The Founder biographical movie. The writer used Holmes’ (2006) theory of features of interactional styles and Holmes' (2006), Kuntjara's (2012), and Paltridge's (2006) theory of gender to support her in conducting this research. The writer transcribed and analyzed Ray Kroc's utterances during business conversations with others for this study, which took a qualitative approach. Facilitative, supportive feedback, conciliatory, indirect, collaborative, person/process-oriented, and affectively oriented are all features of feminine interactional styles used by Ray Kroc. He also demonstrated all masculine interactional styles features, including competitive, aggressive interruptions, confrontational, direct, autonomous, task/outcome-oriented, and referentially oriented. The findings of this study support Holmes' (2006) observation that men and women can use both feminine and masculine interactional styles depending on the situation in the workplace. Ray Kroc, a competitive and masculine man, used feminine and masculine interactional styles to keep his relationships with his partners strong and achieve his business conversation goals at the same time. Moreover, further research for the film The Founder or other movie that focuses on other characters, situations, and theories is recommended.